2020
DOI: 10.1029/2020jb019643
|View full text |Cite
|
Sign up to set email alerts
|

Resolvability of the Centroid‐Moment‐Tensors for Shallow Seismic Sources and Improvements From Modeling High‐Frequency Waveforms

Abstract: Shallow earthquakes in the depth range 0–30 km make up more than 60% of all world's earthquakes. However, resolving their seismic source parameters such as the depth and moment tensor components presents a challenge. Here, we investigate the effect of frequencies higher than 0.025 Hz on centroid‐moment‐tensor inversion for the earthquakes occurring in the top 10 km of the Earth's crust. For a synthetic source located at the depth of 1 km, the maximum amplitude of ground motion due to a vertical dip‐slip mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…However, in regions with strong heterogeneities, such as thick sediments and subducting oceanic plates, focal mechanisms could be incorrectly estimated using conventional CMT methods with a 1D velocity model. To address this issue, the CMT inversion based on Green's functions using the local/regional 3D model has been developed in such regions (e.g., Lee et al 2013;Hejrani et al 2017;Okamoto et al 2018;Takemura et al 2018aTakemura et al , 2018bTakemura et al , b, 2020Wang and Zhan 2020;Hejrani and Tkalčić 2020). By using the 3D CMT results of moderate earthquakes along the Nankai Trough, Takemura et al (2020) demonstrated that the differences in centroid depths and focal mechanisms between 1D and their 3D CMT solutions were significant for offshore earthquakes due to offshore heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…However, in regions with strong heterogeneities, such as thick sediments and subducting oceanic plates, focal mechanisms could be incorrectly estimated using conventional CMT methods with a 1D velocity model. To address this issue, the CMT inversion based on Green's functions using the local/regional 3D model has been developed in such regions (e.g., Lee et al 2013;Hejrani et al 2017;Okamoto et al 2018;Takemura et al 2018aTakemura et al , 2018bTakemura et al , b, 2020Wang and Zhan 2020;Hejrani and Tkalčić 2020). By using the 3D CMT results of moderate earthquakes along the Nankai Trough, Takemura et al (2020) demonstrated that the differences in centroid depths and focal mechanisms between 1D and their 3D CMT solutions were significant for offshore earthquakes due to offshore heterogeneities.…”
Section: Introductionmentioning
confidence: 99%
“…detailed information of ring-faulting, shorter-period seismic waves may be utilized with heterogeneous 3-D velocity structures around the calderas (e.g., Contreras-Arratia and Neuberg, 2019;Hejrani and Tkalčić, 2020). Also, recent studies demonstrated that inversion analysis using a simple 1-D Earth model can affect the MT inversion results (Hjörleifsdóttir and Ekström, 2010;Hejrani et al, 2017); hence, effects of the 3-D velocity structures on the resolvable moment tensors need to be further examined.…”
Section: Accepted Articlementioning
confidence: 99%
“…The correlated waveforms make it hard to distinguish source processes such as reservoir pressurization, crack opening or closing, or shear slip around a ring fault (Fukao et al, 2018;. The combined issues of indeterminate focal depth and weak excitation for shallow source can be overcome using higher frequency waves up to 0.15 Hz; However, the trade-off issue between the volumetric component and vertical CLVD still remains (Hejrani and Tkalčić, 2020). Characterization of non double-couple sources can be improved by increasing the coverage of the source focal sphere.…”
Section: Introductionmentioning
confidence: 99%